How to change the world in 12 easy steps : inspired by the life lessons of Eva Mozes Kor - Tierney, Peggy (Tanglewood, 2021)
"How to Change the World in 12 Easy Steps was inspired by Eva Kor, a child survivor of Auschwitz. She always stressed to young audiences that even though a child, they had the power to change the world. Easy, simple gestures from picking up a piece of trash on the sidewalk, tidying a bedroom, accepting someone who is different, along with other gestures of kindness and thoughtfulness can make a big difference. The book could also serve as a starting point for a conversation on prejudice. Marie Letourneau's illustrations capture the warmth at the heart of this book, making it a fun, but life-changing read"--